Analisis Kesalahan Morfosintaksis Pada Karangan Narasi Siswa Kelas X Seni Rupa SMKN 9 Surakarta - Ridyawati, Isti, Drs. Yakub Nasucha, M. Hum, Laili Etika Rahmawati, S.Pd, M.Pd (2015)
Indonesian as the national language and the language of the country has taught at all levels of education, from elementary school level up to college level. Yet most students, especially students from elementary, junior high school, and even senior high school are not able to use the Indonesian language properly. In Indonesian learning, there are a lot of students still make some mistakes in speech. Speech error not only founded in the talk but also in the written language. One of the written language mistakes that the students made is a morphosyntax mistake. The purpose of this study is to describe the morphosyntax errors and things that are behind the occurrence of morphosyntax errors made by students of X grade at Seni Rupa Vocational High School 9 Surakarta. The type of this research is qualitative research. The data in this study were in the form of a language error in the field of morphosyntax from the narrative essay in X grade at Seni Rupa Vocational High School 9 Surakarta. Data collected by the observe, record, and interviews technique. The results showed that there were 8 language errors contained in the narrative essay of X grade at Seni Rupa. The Errors among: 1 error in writing combination between prefixes meN- with -kan, 1 in writing prefixes ter-, 1 writing combination of prefix di- with the suffix -kan, 15 use of prefixes ber-, 1 use of suffixes -nya, 10 disappearances of prefix meN- , 70 next words writing, and 14 errors for redundancy. As for the things that are behind the occurrence of morphosyntax errors made by students X grade at Seni Rupa Vocational High School 9 Surakarta is that habit, which is less precise language teaching since Elementary School or Junior High School, and the influence of slang language.